The price of non-genetically modified (non-GM) food. (July 2018) - Kalaitzandonakes, Nicholas; Lusk, Jayson; Magnier, Alexandre
Highlights: Added costs for non-GM ingredients and changes in demand for non-GM foods determine non-GM price premiums. Non-GM price premiums were stable over the 8 year period of analysis. US Consumers have been paying price premiums of 10–62% for the non-GM products analyzed. The cost of mandatory labeling of GM foods depends on manufacturer decisions. If food manufacturers reformulate with non-GM ingredients, costs to consumers could be substantial.